(untitled) (Global Journal of Human-Social Science, 2025)
This study seeks is a research on the migration of Cearenses to the municipality of Governador Valadares-MG known for being an international emigration center Bibliographical and documentary research and a field work are its methodology The outcome of this research shows that the Cear s community created spaces reproducing its original culture and keeping its own identity alive These migrants created a territory with hybrid characteristics living in a constant multiterritoriality